1989
DOI: 10.1002/qsar.19890080302
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity of Di‐ and Tripeptides Having Unionizable Side Chains and Correlation with Substituent and Structural Parameters

Abstract: After establishing experimental conditions to obtain a reliable partition ratio, P', we measured the value of 59 di‐ and tripeptides composed of amino acids having unionizable side chains in a 1‐octanol/pH 7.0 aqueous phosphate buffer system in order to approximate the true partition coefficient. We then formulated an equation correlating the variations of log P' (pH 7) among peptides with free‐energy‐related physicochemical parameters for the side chain substituents and substructures. The log P' value of di‐ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 27 publications
(12 reference statements)
2
40
0
Order By: Relevance
“…The use of a zwitterionic buffer avoids the formation of ion pairs with ionized peptides, which would partition into the org. phase [6]. The speed of rotation was set at 1000 rpm and the applied flow rate between 0.3 and 6.5 ml/min.…”
Section: Measurement Of Distribution Coefficients (Log D Values) Octmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a zwitterionic buffer avoids the formation of ion pairs with ionized peptides, which would partition into the org. phase [6]. The speed of rotation was set at 1000 rpm and the applied flow rate between 0.3 and 6.5 ml/min.…”
Section: Measurement Of Distribution Coefficients (Log D Values) Octmentioning
confidence: 99%
“…The studies of Akamatsu et al [6] [8] contain 32 free dipeptides and 38 free tripeptides. We extended this database by measuring the log D values at pH 7.0 of 11 free dipeptides and 10 free tripeptides using centrifugal partition chromatography.…”
mentioning
confidence: 99%
“…The sequences and the logP value of the studied peptides were collected from the literature [1][2][3][4][5], which can be seen in Table 4. …”
Section: Logp For Unblocked Dipeptidesmentioning
confidence: 99%
“…Therefore, it is important meaningful to study the relationships between peptide logP and its structure by theory tool both in academic significance and application value. The literatures [1][2][3][4][5] built a linear model for calculation of logP by the hydrophobic parameter  and index variable of amino acids. Tao Peng et al [6] had been constructed the multivariate linear regression logP prediction model of peptides using the contribution addition method of amino acid side chain.…”
Section: Introductionmentioning
confidence: 99%
“…The very recent interest of medicinal chemists for peptides explains the poor number of studies reported in the literature so far to predict their lipophilicity [9][10][11][12]. Nowadays, peptide lipophilicity prediction is mostly performed by using algorithms developed for organic molecules.…”
Section: Introductionmentioning
confidence: 99%